2017
DOI: 10.1093/pcp/pcx175
|View full text |Cite|
|
Sign up to set email alerts
|

MiR858-Mediated Regulation of Flavonoid-Specific MYB Transcription Factor Genes Controls Resistance to Pathogen Infection in Arabidopsis

Abstract: MicroRNAs (miRNAs) are a class of short endogenous non-coding small RNAs that direct post-transcriptional gene silencing in eukaryotes. In plants, the expression of a large number of miRNAs has been shown to be regulated during pathogen infection. However, the functional role of the majority of these pathogen-regulated miRNAs has not been elucidated. In this work, we investigated the role of Arabidopsis miR858 in the defense response of Arabidopsis plants to infection by fungal pathogens with necrotrophic (Ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…RNS1 expression is also associated to wounding induced local and systemic signaling (Lebrasseur et al, 2002), and correlates with the accumulation of specific tRNA fragments (Megel et al, 2019). The role of the other identified ribonuclease, PR4, is less known, its expression is associated with SAR (Mishina and Zeier, 2007), and its induced by ethylene and SA (Potter et al, 1993;Camargo-Ramírez et al, 2018).…”
Section: Proteins That Accumulate In the Apoplast Of Senescent Leavesmentioning
confidence: 99%
“…RNS1 expression is also associated to wounding induced local and systemic signaling (Lebrasseur et al, 2002), and correlates with the accumulation of specific tRNA fragments (Megel et al, 2019). The role of the other identified ribonuclease, PR4, is less known, its expression is associated with SAR (Mishina and Zeier, 2007), and its induced by ethylene and SA (Potter et al, 1993;Camargo-Ramírez et al, 2018).…”
Section: Proteins That Accumulate In the Apoplast Of Senescent Leavesmentioning
confidence: 99%
“…6). Most of them play critical roles in plant defense against biotic stress in previous reports [7,[31][32][33][34], and many were induced by E. ampelina infection in the HR grape at the earlier stages (Fig. 6).…”
Section: Transcription Factorsmentioning
confidence: 61%
“…Recently, miR398 was found to be involved in immunity against the blast fungus through regulating two genes encoding Cu/Zn-superoxidase dismutase (CSD) [35]. Besides, miR858-mediated regulation of phenylpropanoid biosynthetic pathway also played important role in Arabidopsis immunity [36]. These results demonstrated that certain interactions between lncRNAs and miRNAs may exist in melon, which provides a solid foundation for further investigation in the function of lncRNAs in PM tolerance.…”
Section: Discussionmentioning
confidence: 85%